Animated algorithms a hypermedia learning environment for Introduction to algorithms - Dynes, Scott; Gloor, Peter; Cormen, Thomas H.; Leiserson, Charles Eric. (Cambridge : MIT Press, 1993)
"An ideal format for the visual exploration of complex algorithms contained in the text Introduction to algorithms by Thomas H. Cormen, Charles E. Leiserson, and Ronald L. Rivest. Contains three complimentary components: a hypertext version of the book itself, interactive animations of the most important algorithms, and movies explaining the use of the hypertext interface and the animations"--P. 3 of booklet
Title from disc label
System requirements: Macintosh II, LC, or Classic II computer; 4M of RAM; CD ROM drive; hard disk; System 6.0.7 (7.0 recommended); QuickTime init
Keywords: Algorithms -- Study and teaching -- Software; Electronic digital computers -- Programming -- Study and teaching -- Software; CD-ROMs.